2011
DOI: 10.1371/journal.ppat.1002061
|View full text |Cite
|
Sign up to set email alerts
|

Kupffer Cells Hasten Resolution of Liver Immunopathology in Mouse Models of Viral Hepatitis

Abstract: Kupffer cells (KCs) are widely considered important contributors to liver injury during viral hepatitis due to their pro-inflammatory activity. Herein we utilized hepatitis B virus (HBV)-replication competent transgenic mice and wild-type mice infected with a hepatotropic adenovirus to demonstrate that KCs do not directly induce hepatocellular injury nor do they affect the pathogenic potential of virus-specific CD8 T cells. Instead, KCs limit the severity of liver immunopathology. Mechanistically, our results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 61 publications
4
84
0
Order By: Relevance
“…The accumulation of virus-nonspecific CD8 + T cells in the liver of chronically infected patients has been linked to signs of active organ damage (6,18,19), and inhibiting the hepatic accumulation of virus-nonspecific CD8 + T cells and other virus-nonspecific inflammatory cells [i.e., CD4 + T cells, neutrophils, dendritic cells, monocytes, natural killer (NK) cells, NKT cells] in mouse models of acute viral hepatitis has been shown to reduce liver disease severity (5,(20)(21)(22)(23). Of note, the recruitment process of virus-nonspecific inflammatory cells into the liver of these animals is different from that of virus-specific CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The accumulation of virus-nonspecific CD8 + T cells in the liver of chronically infected patients has been linked to signs of active organ damage (6,18,19), and inhibiting the hepatic accumulation of virus-nonspecific CD8 + T cells and other virus-nonspecific inflammatory cells [i.e., CD4 + T cells, neutrophils, dendritic cells, monocytes, natural killer (NK) cells, NKT cells] in mouse models of acute viral hepatitis has been shown to reduce liver disease severity (5,(20)(21)(22)(23). Of note, the recruitment process of virus-nonspecific inflammatory cells into the liver of these animals is different from that of virus-specific CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…chemokines and damage-associated molecular pattern molecules whose hepatic expression/release follows hepatocellular antigen recognition by the virus-specific CD8 + T cells (5,(20)(21)(22)(23), and the latter significantly depends on platelets. Indeed, using HBV transgenic mice as recipients of HBV-specific CD8 + T cells and mice acutely infected with adenovirus, we recently showed that platelets are detectable within CD8 + T cell-containing hepatic necroinflammatory foci and that their selective depletion profoundly ameliorates the severity of liver disease (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many models of liver injury, hepatic macrophages themselves are involved in the pathogenesis of the liver damage (31). In other models, macrophages play a role in preventing severe hepatic immunopathology (32) or in limiting the severity of liver immunopathology (33). These particular mechanisms do not appear to play a significant role in our HBV model, as mice lacking macrophages or CXCL13/CXCR5 did not have a significant difference in liver injury, despite developing significantly different immune responses to HBV (Figures 3, 5, and 6).…”
Section: Discussionmentioning
confidence: 99%
“…To test whether KCs were important for inducing P25 T cell activation, we injected rAAVtreated mice with clodronate liposomes before T cell transfer at an i.v. dose that depletes KCs while sparing hepatic CD11c high DCs (28). This treatment resulted in efficient specific depletion of F4/80 + cells (Fig.…”
Section: Intrahepatic P25 Activation Was Mediated By Liver Phagocyticmentioning
confidence: 92%